PENGELOLAAN TERHADAP PERUBAHAN DAN PERKEMBANGAN ORGANISASI - Muhammad rifa'i (Universitas Islam Negeri Sumatera Utara Medan, 2017)
The changing of the organisms do not do to balance the changing and demanding of the anti-dynastic and developing world, to conduct organizational change, do the non-organization changing must be done by managing carefully. Do the changing and devolvement to the organization needs a careful planning. The ready resource to inform the changing and development to be able to create youth and it is from organization culture which supports the individual activities, and a group in the organization. In changing and developing of organization and get resistance. The constraints and challenges of internal and external organization, on the other hand lead a conflict in organization. The management of changing and development of organization carefully and calculation are able to take the organization survive and compete with presenting various organization which apply the changing organization system with the international standard.